A Novel Compound Analgesic Cream (Ketamine, Pentoxifylline, Clonidine, DMSO) for Complex Regional Pain Syndrome Patients. Issue 1 (7th November 2015) - Russo, Marc A.; Santarelli, Danielle M.
Abstract: Background: Evidence suggests that complex regional pain syndrome (CRPS) is a manifestation of microvascular dysfunction. Topical combinations of α2‐adrenergic receptor agonists or nitric oxide donors with phosphodiesterase or phosphatidic acid inhibitors formulated to treat microvascular dysfunction have been shown to reduce allodynia in a rat model of CRPS‐I. Driven by these findings, we assessed the outcomes of CRPS patients treated with a compound analgesic cream (CAC) consisting of ketamine 10%, pentoxifylline 6%, clonidine 0.2%, and dimethyl sulfoxide 6% to 10%. Methods: An audit was conducted on 13 CRPS patients who trialed the CAC. A detailed report was compiled for each patient which comprised baseline characteristics, including CRPS description, previous treatments, and pain scores (numerical pain rating scale; 0 to 10). Recorded outcomes consisted of pain scores, descriptive outcomes, and concurrent medications/treatments, for which basic analysis was performed to determine the effectiveness of the CAC. Case reports are presented for 3 patients with varying outcomes. Results: Nine patients (69%) reported pain/symptom reduction (4.4 ± 2.1 vs. 6.3 ± 1.9) with use of the CAC. Six patients reported sustained benefits after 2 months of CAC use, and 2 patients reported complete resolution of pain/symptoms: one had early CRPS‐I and the other received a partial CRPS diagnosis. An otherwise medication refractory and intolerant patient found partial benefit with the CAC. Conclusions: These results demonstrate promise for this topical combination as a useful treatment in multimodal therapy for patients with CRPS, with the potential to resolve pain/symptoms in early CRPS patients.